Konsep Ikhlas Menurut Imam Al-Ghazali dan Relevansinya Terhadap Tujuan Pendidikan Islam - Nurul Hidayah; Ade Rizal Rosidi; Amrini Shofiyani (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
The purpose of this study is to determine the concept of sincerity according to Imam Al-Ghazali and its relevance to the goals of Islamic education. Talking about traits that are very easy to say but, in essence, very difficult to do, namely sincerity, Sincerity is an intention from the heart that is then applied to the form of deeds, whose main purpose is for Allah SWT. Sincerity is indeed very easy to say but contains enormous rewards if someone succeeds in passing the sincere certification. The method used in this research is to use the literature review method, namely by reviewing various books, manuscripts, and scriptures that are available to serve as data sources. So that the results of this study can be understood, the concept of sincerity according to Imam Al-Ghazali is to cleanse all deeds from other intentions, both a little and a lot as a whole, so that these deeds are done with the intention of getting closer to Allah. The relevance of sincerity to the goals of Islamic religious education lies in the aspect of religious goals, which make Allah the God who must be worshiped without anyone partnering with him, and also in the aspect of mundane goals, where the emphasis is on all worldly activities, namely studying and working, both of which must be based on sincerity.